Biomarkers of tolerance and immunological monitoring in liver transplantation - V. E. Syutkin; N. V. Borovkova; M. S. Novruzbekov (Трансплантология (Москва))
Introduction. We reviewed the literature data on clinical and laboratory parameters that allow predicting the development of operational tolerance in liver transplant recipients after their complete weaning from immunosuppressive therapy. The aim was to identify possible biomarkers of tolerance in liver transplant recipients with the successful complete weaning from immunosuppression for subsequent implementation in routine clinical practice. The cellular, humoral, and molecular markers of the liver transplant recipients who were completely withdrawn from immunosuppressive therapy without the development of graft dysfunction were estimated. The authors underlined the necessity of clinical trials for identifying biomarkers of the operational tolerance development.